2014
DOI: 10.2337/dc14-1121
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Statin Therapy Alters the Natural History of Diabetic Coronary Atherosclerosis: Insights From SATURN

Abstract: OBJECTIVEAlthough statins can induce coronary atheroma regression, this benefit has yet to be demonstrated in diabetic individuals. We tested the hypothesis that highintensity statin therapy may promote coronary atheroma regression in patients with diabetes. RESEARCH DESIGN AND METHODSThe Study of Coronary Atheroma by Intravascular Ultrasound: Effect of Rosuvastatin Versus Atorvastatin (SATURN) used serial intravascular ultrasound measures of coronary atheroma volume in patients treated with rosuvastatin 40 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 34 publications
3
37
1
Order By: Relevance
“…Huang and Chen (1) in our article (2). We agree that the diabetic population is heterogeneous in terms of cardiovascular risk, with varying comorbidities and duration and severity of diabetes per se.…”
supporting
confidence: 57%
“…Huang and Chen (1) in our article (2). We agree that the diabetic population is heterogeneous in terms of cardiovascular risk, with varying comorbidities and duration and severity of diabetes per se.…”
supporting
confidence: 57%
“…4 In addition, advances in medical therapy including high-dose statins seem to mitigate the markedly accelerated progression of native atherosclerosis in diabetic patients. 5 Intriguingly, although diabetes mellitus has historically been considered a powerful Background-Diabetes mellitus and angiographic coronary artery disease complexity are intertwined and unfavorably affect prognosis after percutaneous coronary interventions, but their relative impact on long-term outcomes after percutaneous coronary intervention with drug-eluting stents remains controversial. This study determined drug-eluting stents outcomes in relation to diabetic status and coronary artery disease complexity as assessed by the Synergy Between PCI With Taxus and Cardiac Surgery (SYNTAX) score.…”
mentioning
confidence: 99%
“…2,3 Finally, between 2 matched groups analysis, Cortese et al registered a significant acute kidney injury reduction (primary end point) in transradial group (8.4% vs 16.9%, p ¼ 0.007) and Thrombolysis In Myocardial Infarction major bleedings (0.3% vs 3%, p ¼ 0.03; secondary end point) although no statistical difference emerged among common major adverse cardiac events and stent thrombosis. Therefore, it cannot be excluded an adjunctive role of bivalirudin to transradial primary percutaneous coronary intervention in lowering incidence of acute kidney injury through in-hospital reduction of overall major hemorrhagic events.…”
Section: About Acute Kidney Injury During Primary Percutaneous Coronamentioning
confidence: 94%
“…There has been significant evidence from previous studies validating the use of total 12-lead QRS voltage in diagnosing LVH, 2 especially in patients with systemic hypertension. 3 The investigators referenced a few studies that reported the total 12-lead QRS voltage as a superior criterion compared with the traditional criteria with cardiac weight at necropsy as a reference. 4 They also point out that this criterion showed a greater performance in obese patients compared with the normal-weight patients where resultant overall performance in predicting LVH was low.…”
Section: About Acute Kidney Injury During Primary Percutaneous Coronamentioning
confidence: 99%